Smooth Sailing or Stormy Seas? Atlantic Canadian Physical Educators on the State and Future of Physical Education - Robinson, Daniel B.; Randall, Lynn (Canadian Journal of Education/Revue canadienne de l’éducation, 2016)
This article summarizes results from a recently completed study that focused upon the current state and possible future of physical education within Canada’s four Atlantic provinces. Data from both large-scale surveys and eight follow-up focus group interviews are shared as they relate to the state and future of physical education, possible reforms in physical education, and two elements of NASPE’s PE2020 framework (physical education teacher education [PETE], curriculum). Results suggest physical educators within Atlantic Canada are largely satisfied with the state of physical education, with few (external) negative observations. Moreover, there is little-to-no perceived need for internal reform within the discipline. Physical educators also provided insightful information related to their beliefs and practices regarding PETE and curriculum. Results might be of particular interest to those similarly engaged in “futures” inquiry within physical education. More specifically, this research attends to the call for physical educator-informed reform efforts.